The Effect of Teacher's Certification on The Performance Results in SD Negeri 040446 Kabanjahe - Sari Jusnita Br Ginting, Gabriela Anjelika Br Sebayang, Monang Tua Simamora (Education Achievement: Journal of Science and Research, 2023)
This study aims to determine the effect between teacher certification on teacher performance in elementary school. This research was conducted at SD Negeri 040446 Kabanjahe in 2023. This research is a type of quantitative research using comparative causal methods or expost facto research. The population in this research is all teachers in SD Negeri 040446 Kabanjahe who have been certified. The sampling technique used is purposive sampling. The subjects in this study were 5 teachers who had passed certification. The object of research is in the form of Teacher Certification and Teacher Performance at SD Negeri 040446 Kabanjahe. The study was conducted from October to November 2023. Data analysis techniques use simple linear regression analysis and multiple linear regression analysis. Based on data analysis, r count 0.887 > r table 0.878, which means that there is a relationship between teacher certification on teacher performance and obtained t count value 2.065 > t table 1.672 and significance t count 0.043 < t table 0.05, which means that there is a significant effect of teacher certification on teacher performance in SD Negeri 040446 Kabanjahe. Based on the similarities in discussion, it can be concluded that there is a positive influence between teacher certification on teacher performance at SD Negeri 040446 Kabanjahe.